As meninas: entre o universo de Lygia Fagundes Telles e o universo das representações femininas (2010) - Oliani, Nara Gonçalves; Franco Júnior, Arnaldo [UNESP] (My University, 2012)
This article is devoted to a brief analysis of representations of women in As meninas, by Lygia Fagundes Telles, focusing on the three main characters of the novel and also on some secondary characters. The novel is set within a context that was characterized by a double crisis: the political crisis arising from authoritarianism and violence of the military dictatorship, and the crisis of the patriarchy system, due to the gradual political and social emancipation of women. Our paper aims to understand, in a succinct way, the critical dialogue established in the novel between the representations of women and that context of the dual crisis that constitute the novelistic material of As meninas

O presente artigo é dedicado a uma breve análise das representações da mulher presentes na obra As meninas, de Lygia Fagundes Telles, enfocando, principalmente, as três personagens protagonistas do romance e, também, algumas personagens secundárias. O romance está inserido em um contexto caracterizado por uma dupla crise: a crise política, decorrente do autoritarismo e da violência da ditadura militar, e a crise do patriarcalismo, decorrente da progressiva emancipação político-social das mulheres. Nosso artigo visa a compreender, de modo sucinto, o diálogo crítico estabelecido, no romance, entre as representações da mulher e este contexto de dupla crise que constituem a matéria romanesca de As meninas.
Keywords: Autoritarismo; Lygia Fagundes Telles; representação feminina; tradição patriarcal; Authoritarianism; Lygia Fagundes Telles; patriarcalism; women representation